Gastrointestinale neuroendokrine Tumoren – Update 2024 - Lahner, Harald; Pavel, Marianne Ellen (Innere Medizin, 2024)
Gastrointestinal neuroendocrine tumours (NETs) are rare and clinically heterogeneous. From a diagnostic perspective, well-differentiated tumours must be distinguished from poorly differentiated neuroendocrine carcinomas. The disease may be associated with autonomous hormone secretion by the tumour, and the resulting syndromes are often associated with reduced survival. Somatostatin analogues form the backbone of antiproliferative and antisecretory treatment alongside local ablative procedures. In pancreatic NET, prospective studies confirm the value of specific chemotherapy, particularly in terms of higher remission rates. New tyrosine kinase inhibitors are an option for patients that have failed to respond to standard treatments. Inhibition of HIF2-alpha is an emerging effective treatment option for patients with von Hippel-Lindau-syndrome associated tumours, e.g. pancreatic NET. Radioligand therapy is an established second-line option for advanced NET of the small intestine, and recent study results support its use in pancreatic NET in earlier-line treatment. Due to the complexity of the disease, management of NET patients should be performed in close collaboration with a specialized multidisciplinary team.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Molecular targeted therapy; Radiofrequency ablation; Radioligand therapy; Somatostatin analogues; Tyrosine kinase inhibitors